Associate Professor Ts. Dr. Norhayati invents water treatment process using resin - Hafizatulazlin, Abdul Aziz; Nur Hartini, Mohd Hatta (2021)
GAMBANG, 6 April 2021 - A lecturer from the Faculty of Chemical & Process Engineering Technology, Universiti Malaysia Pahang (UMP), Associate Professor Ts. Dr. Norhayati Abdullah, 42, conducted research on the water treatment process using resin.